The Contribution of Hotel Tax to Regional Tax in Makassar City of South Sulawesi - Usman, Usnirati; Hersanti P, Mahardian; Sari, Sri Nirmala (Patria Artha Journal of Accounting dan Financial Reporting, 2017)
This research reviews about the hotel tax contribution to regional tax Makassar City. The purpose of this study was to determine how the contribution of the hotel tax to the regional tax Makassar City 2011-2012.This research uses descriptive quantitative method. The data used is primary and secondary data. Primary data were obtained through documentation and interview with the employees of the Tax Division I Hotel and Entertainment Regional Revenue Office Makassar. Secondary data about hotel tax revenue from 2011 to 2015, regional taxes from 2011 to 2015, and the number of hotels in the city of Makassar based classification 2011-2015.The results of the research contribution of the hotel tax to the regional tax in the city of Makassar by calculating the percentage contribution of the hotel tax to the regional tax Makassar, fluctuating within a period of five years. Hotel tax contribution in 2011 amounted to 12.94% (less), in 2012 amounted to 9.7% (very less), in 2013 amounted to 8.58% (very less), in 2014 amounted to 8.99% (very less), and in 2015 amounted to 7.88% (very less). It is influenced by the ratio of the number of hotel and the number of residential its not logical, and the rapid growth of the hotel business which leads to high competition among hotels. Hotel tax contribution to regional tax years 2011-2015 is still relatively less.